2010
DOI: 10.1007/s00432-010-0805-z
|View full text |Cite
|
Sign up to set email alerts
|

Identification of proteins responsible for the multiple drug resistance in 5-fluorouracil-induced breast cancer cell using proteomics analysis

Abstract: MDR of MCF-7/5-FU likely associated with differentially expressed proteins and 14-3-3sigma may play a positive role in chemotherapy. These findings may provide theoretical support for the prediction of chemotherapeutic response and reverse of MDR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…To search biomarkers associated with tamoxifen therapy resistance in recurrent breast cancer, comparative proteomics was performed on LCM-purified breast tumor cells from tamoxifen-sensitive and -resistant human breast tumors, and a set of putative biomarkers (extracellular matrix metalloproteinase inducer, ENPP1, EIF3E, and GNB4) associated with tamoxifen resistance in the recurrent breast cancer were revealed and validated by tissue microarray in an independent patient cohort [41]. In several studies, 14-3-3σ overexpression was found as a biomarker for drug resistance in human breast cancer [26,42].…”
Section: Breast Cancermentioning
confidence: 99%
“…To search biomarkers associated with tamoxifen therapy resistance in recurrent breast cancer, comparative proteomics was performed on LCM-purified breast tumor cells from tamoxifen-sensitive and -resistant human breast tumors, and a set of putative biomarkers (extracellular matrix metalloproteinase inducer, ENPP1, EIF3E, and GNB4) associated with tamoxifen resistance in the recurrent breast cancer were revealed and validated by tissue microarray in an independent patient cohort [41]. In several studies, 14-3-3σ overexpression was found as a biomarker for drug resistance in human breast cancer [26,42].…”
Section: Breast Cancermentioning
confidence: 99%
“…Proteomics has been showed to be a promising method in breast cancer marker candidate (Fan et al 2010;Zheng et al 2010;Xu et al 2010). In recent years, as liquid chromatography and mass spectrometry methodologies have improved, interest in the proteomic analysis of human sera has increased Zolotarjova et al 2005;Freeman et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…That could therefore participate in the anti-apoptotic function of this receptor. A comparative study demonstrated that cytokeratin-8 could be involved in drug resistance mechanisms, and more precisely to the 5-FU resistance of MCF-7 cells, with a potential relation with 14-3-3sigma (Zheng et al, 2010). Concerning cytokeratin-19 it has been reported that this protein can be secreted in the extracellular matrix and have a pro-metastatic effect (Alix-Panabieres et al, 2009).…”
Section: Fig 6 Maldi-tof and Ms-ms Spectra Corresponding To Hsp27 mentioning
confidence: 99%